THE RISE OF STREAMING PLATFORMS IN NIGERIA: EFFECT ON AUDIENCE BEHAVIOUR AND TELEVISION REVENUE - Onasanya, Favour Abiola; Ilupeju, Oluwadarasimi; Adelabu, Taofeek Omowale (African Journal of Social and Behavioural Sciences, 2025)
The rise of streaming services has significantly altered the media consumption landscape, shifting audiences from traditional television to on-demand content. This study examines the factors driving this transition and its impact on the revenue and audience behaviour of television stations in Nigeria. Anchored in Uses and Gratifications Theory and Disruptive Innovation Theory, the research examines how streaming platforms cater to evolving viewer preferences while challenging traditional broadcasting models. A mixed-method approach was employed, incorporating surveys and expert interviews. Data was collected from 400 respondents, including students, working professionals, and media industry stakeholders, using stratified sampling. Key focus areas include streaming habits, platform preferences, and content engagement patterns. Findings revealed that 67% of respondents prefer streaming over traditional television, citing affordability, content flexibility, and convenience as primary drivers. Additionally, advertising revenue for TV stations has declined by 25% in the last five years, prompting broadcasters to explore digital integration strategies. The study highlights the need for hybrid broadcasting models, leveraging both linear and digital platforms to remain competitive. It also recommends regulatory interventions to ensure fair competition between local broadcasters and international streaming services. By adapting to these changes, Nigerian television stations can sustain relevance in the evolving digital media ecosystem.